Barriers to tuberculosis case finding in primary and secondary health facilities in Ghana: perceptions, experiences and practices of healthcare workers - Joyce B. Der; Alison D. Grant; Daniel Grint; Clement T. Narh; Frank Bonsu; Virginia Bond (BMC, 2022)
Abstract Background Ghana's national tuberculosis (TB) prevalence survey conducted in 2013 showed higher than expected TB prevalence indicating that many people with TB were not being identified and treated. Responding to this, we assessed barriers to TB case finding from the perspective, experiences and practices of healthcare workers (HCWs) in rural and urban health facilities in the Volta region, Ghana. Methods We conducted structured clinic observations and in-depth interviews with 12 HCWs (including five trained in TB case detection) in four rural health facilities and a municipal hospital. Interview transcripts and clinic observation data were manually organised, triangulated and analysed into health system-related and HCW-related barriers. Results The key health system barriers identified included lack of TB diagnostic laboratories in rural health facilities and no standard referral system to the municipal hospital for further assessment and TB testing. In addition, missed opportunities for early diagnosis of TB were driven by suboptimal screening practices of HCWs whose application of the national standard operating procedures (SOP) for TB case detection was inconsistent. Further, infection prevention and control measures in health facilities were not implemented as recommended by the SOP. HCW-related barriers were mainly lack of training on case detection guidelines, fear of infection (exacerbated by lack of appropriate personal protective equipment [PPE]) and lack of motivation among HCWs for TB work. Solutions to these barriers suggested by HCWs included provision of at least one diagnostic facility in each sub-municipality, provision of transport subsidies to enable patients' travel for testing, training of newly-recruited staff on case detection guidelines, and provision of appropriate PPE. Conclusion TB case finding was undermined by few diagnostic facilities; inconsistent referral mechanisms; poor implementation, training and quality control of a screening tool and guidelines; and HCWs fearing infection and not being motivated. We recommend training for and quality monitoring of TB diagnosis and treatment with a focus on patient-centred care, an effective sputum transport system, provision of the TB symptom screening tool and consistent referral pathways from peripheral health facilities.